An interdisciplinary understanding of energy citizenship: Integrating psychological, legal, and economic perspectives on a citizen-centred sustainable energy transition. (March 2023) - Hamann, Karen R.S.; Bertel, Maria P.; Ryszawska, Bożena; Lurger, Brigitta; Szymański, Piotr; Rozwadowska, Magdalena; Goedkoop, Fleur; Jans, Lise; Perlaviciute, Goda; Masson, Torsten; Fritsche, Immo; Favaro, Tamara; et al.
Abstract: Energy citizenship is an emerging concept in policy and practice. Yet scientific theorising around energy citizenship is scarce, and rarely bundled in interdisciplinary discourse. In this article, we present an interdisciplinary definition of energy citizenship as people's rights to and responsibilities for a just and sustainable energy transition. Energy citizenship contains multiple aspects and allows for various approaches, of which we zoom into psychological, legal, and economic perspectives on the topic. From a psychological perspective, we construct an empirically testable sub-definition of energy citizenship based on previous psychological theorising. A legal perspective shows, exemplarily for the EU context, that energy citizenship qualifies as an EU citizenship because it consists of a bundle of rights and duties of the individual in the context of a committed, just and sustainable energy transition. An economic perspective reveals how energy citizenship already takes shape in current EU directives, and how this implies a new – more collectivist – economic model. Drawing on the three perspectives, we then sketch energy citizenship as an interdisciplinary research field. As a conclusion, we present a transdisciplinary definition of energy citizenship that is suitable for policy makers, energy communities and citizens, as it explicates a co-responsible process of people and governments.